20y-16=18y-9

Simple and best practice solution for 20y-16=18y-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20y-16=18y-9 equation:


Simplifying
20y + -16 = 18y + -9

Reorder the terms:
-16 + 20y = 18y + -9

Reorder the terms:
-16 + 20y = -9 + 18y

Solving
-16 + 20y = -9 + 18y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-18y' to each side of the equation.
-16 + 20y + -18y = -9 + 18y + -18y

Combine like terms: 20y + -18y = 2y
-16 + 2y = -9 + 18y + -18y

Combine like terms: 18y + -18y = 0
-16 + 2y = -9 + 0
-16 + 2y = -9

Add '16' to each side of the equation.
-16 + 16 + 2y = -9 + 16

Combine like terms: -16 + 16 = 0
0 + 2y = -9 + 16
2y = -9 + 16

Combine like terms: -9 + 16 = 7
2y = 7

Divide each side by '2'.
y = 3.5

Simplifying
y = 3.5

 

You can always share this solution

See similar equations:

| a=0.6a+85000 | | (10+8)+5x(10-7)= | | 5x+6=83-6x | | 4Y-7=5-2Y | | 5X+3=6X-2 | | 8x-5=2(3x-6) | | 7=-16t^2+10t+8 | | 0=-16t^2+10t+8 | | 0=16t^2+10t+8 | | -8n-4=-2+n-6-8n | | 6x^2+19x+5=0 | | n-5=-39 | | n+-73=27 | | n-28=-2 | | N+67=-34 | | lny(3-lny)=2 | | p^5-6p^3+8p=0 | | 5x+6x+14=8 | | (3x+10)=8x | | 3x+10=8x | | 50-3x=7x+80 | | 9+4x=-15-2 | | 9+4x=15-2 | | 9+4X=15-2x | | 11x=8x-3(5-3x) | | y=x^2-7 | | 3m+7=-3(m+7)-m | | y=7x | | 2x^2+6x=8 | | 5x^2+11x=0 | | 5x+11x=0 | | 2x+3y+5z=27 | | 4(15-12x)-8(7.5-3x)+25x=5*5*5*5 | | 4x-2x-2=-42 | | 4-3(2+x)=x | | 3c+2=4c-9 | | 27(13-18x)-54(18-9x)+388-(-222-x)=2(x-11) | | -11-Sa=6(5a+4) | | (19+4x)=x+(19+4x) | | 9-12x=(4-3x)-(9x+7) | | x-(17x+32)=4-(17x+32) | | 3(2x+x)=8x | | 16y-2=(30y-20-15y)+30 | | 3(9+14)=x-12 | | 8(4k-4)=-5k+32 | | 15=19-3k-31 | | (7+3)x=24+9x | | 0.25z-24=(16-0.75z)-15 | | 26-(26-6x)=4x+(2+x) | | 77=7x | | 6+10x+2=6x+(8+4x) | | (24x+3)+46=86-(24-23x) | | 13y+5=40+12y+25 | | 7x+14-12=16+6x | | (2+8)*2+3-2*4+7+19(7*2+3)+5= | | 24-7x+3=-8x+36 | | 6+-2x= | | 14+2x-6=3x+13-2x | | 24-3x=26-4x | | 7x-42=6x+12 | | 16+9x=8x+18 | | -5-(7x+2)= | | 5x-36=22+4x | | 2p+11.4=6-p*2.4 | | 11d+33=15d |

Equations solver categories